Von Willebrand disease type 2N in a neonate: A case report (Indian Journal of Child Health, 2020)
The occurrence of von Willebrand disease (VWD) is relatively uncommon. Type 1 is more prevalent than the other types. The disease prevalence is about only 1%, in which type 1 includes 60–80% of the cases, type 2 includes 20–30% of cases, and type 3 accounts for <5% of the cases. It mainly arises due to homozygous or composite heterozygous mutations in the von Willebrand factor gene (12p13.3) leading to synthesis of a truncated protein or allele silencing. We report a case of newborn 34-week gestation who presented with abdominal distension with melena and seizures. The child’s plasma was studied and it revealed VWD.